Coordination among Agencies delivering Extension Services under Agricultural Technology Management Agency - V.Lenin,; Baldeo Singh,; K. Vijayaragavan, (Journal of Agricultural Extension Management, 2025)
In the late Nineties the World Bank funded a new extension delivery mechanism in India, called Agricultural Technology Management Agency (ATMA). Since 2005, ATMA is being fully funded by the Government of India. One of the key features of ATMA is the financial sustainability of • the system. To ensure financial sustainability, the high recurring cost incurred in the T&V system in the form of establishment costs was controlled in ATMA by not recruiting additional staff. To meet the shortfall of extension personnel, private agencies and NGOs were roped in. All the agencies delivering extension services were linked. This study was conducted with the objective of investigating the extent and factors of coordination among various agencies involved in delivery of extension services. Ahmednagar district of Maharashtra state and Dahod district of Gujarat state were purposively selected and sixty ATMA staff were interviewed. Resources, relations and performance; necessity and adaptability; values; information; and infrastructure were the factors of coordination. Majority of the ATMA staff of Ahmednagar and Dahod districts expressed that coordination among agencies delivering extension services was high.